Efficacy and safety of camrelizumab plus Lacticaseibacillus paracasei in the treatment of advanced esophageal squamous cell carcinoma: A single-arm, single-center, exploratory trial - Tengfei Zhang; Kang Cui; Xiaodan Liu; Yikai Han; Lin Li; Jinhui Xie; Xiangwen Dong; Yuhan Bao; Shengju Ren; Ziwen Lei; Pu Yu; Huan Zhao; et al. (Cancer Pathogenesis and Therapy)
Background: Esophageal cancer (EC) is the seventh most prevalent cancer and the sixth most common cause of cancer-related mortalities worldwide. Camrelizumab, a monoclonal antibody, has demonstrated moderate efficacy in esophageal squamous cell carcinoma (ESCC). Lactobacillus paracasei, a probiotic bacterium, has a complementary effect in immunotherapy. This study aimed to evaluate the combination of camrelizumab and L. paracasei for advanced ESCC. Methods: This single-arm, single-center, exploratory trial was conducted at the First Affiliated Hospital of Zhengzhou University, Zhengzhou, China. Eligible patients received 200 mg camrelizumab biweekly and two bags of L. paracasei twice daily. The primary endpoint was progression-free survival (PFS), and the secondary endpoints were disease control rate (DCR), overall survival (OS), objective response rate (ORR), and adverse events (AEs). Results: From May 2020 to October 2022, ten patients with advanced ESCC who did not respond to first-line therapy were admitted. At the data cutoff date (August 9, 2023), the median follow-up duration was 12 months. Two of 10 (20%) achieved objective responses. The median survival was 7.5 months and the median OS was not reached. Grade 3 treatment-related AEs occurred in two of the 10 patients (20%). No serious treatment-related AEs or deaths occurred. Conclusions: Camrelizumab combined with L. paracasei showed favorable anticancer activity and may be a viable second-line treatment for patients with ESCC. Trial registration: ChiCTR2000032093, https://www.chictr.org.cn.